2021
DOI: 10.3389/fcell.2021.708715
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Imaging Reveals Rapid Estradiol Action on the Surface Movement of AMPA Receptors in Live Neurons

Abstract: Gonadal steroid 17β-estradiol (E2) exerts rapid, non-genomic effects on neurons and strictly regulates learning and memory through altering glutamatergic neurotransmission and synaptic plasticity. However, its non-genomic effects on AMPARs are not well understood. Here, we analyzed the rapid effect of E2 on AMPARs using single-molecule tracking and super-resolution imaging techniques. We found that E2 rapidly decreased the surface movement of AMPAR via membrane G protein-coupled estrogen receptor 1 (GPER1) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…On one hand, the MLE does not reveal any significant effect due to E2 treatment, on the other hand the application of E2 significantly decreases the diffusion coefficients based on statistics on the MSD results. Previous study ( Godó et al, 2021 ) has shown that GPER1 internalization depletes the GPER1 which is crucial for the effectiveness of E2 in soma, indicating the propriety of MLE based result.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…On one hand, the MLE does not reveal any significant effect due to E2 treatment, on the other hand the application of E2 significantly decreases the diffusion coefficients based on statistics on the MSD results. Previous study ( Godó et al, 2021 ) has shown that GPER1 internalization depletes the GPER1 which is crucial for the effectiveness of E2 in soma, indicating the propriety of MLE based result.…”
Section: Resultsmentioning
confidence: 84%
“…The result of MLE can be surprising as the lower E2 concentration (100 pM) evoked a significant decrease of the diffusion coefficients, while the administration of the higher dose of E2 (100 nM) did not induce any change. This effect was previously investigated ( Godó et al, 2021 ) and it was revealed that the difference may be the consequence of GPER1 internalization in the soma induced by 100 nM E2. It was also demonstrated that both ERβ and GPER1 are required for the effect of E2.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations